Comparison of fascicle behaviors between superficial and deeper muscles of triceps brachii during isometric contractions. (October 2020) - Akima, Hiroshi; Maeda, Hisashi; Koike, Teruhiko; Ishida, Koji; Ando, Ryosuke
Abstract: Purpose: We assessed fascicle behaviors of the upper extremities during isometric contractions at different joint angles in this study. Methods: Thirteen healthy men and women performed isometric elbow extension tasks at 50% and 75% of maximal voluntary contraction (MVC) at 60°, 90°, and 120° of elbow extension (full extension = 180°). Extended field-of-view B-mode ultrasonography was used to obtain sagittal plane panoramic images of the long head (TB-Long) and medial head (TB-Med) of the triceps brachii at rest and during contraction; fascicle length and pennation angle were measured. Results: In the TB-Long, significant fascicle shortening from rest was found during 50% and 75%MVC at 60° and during 75%MVC at 90° of extension. There was no significant fascicle shortening in the TB-Med muscle under any conditions. There was no significant pennation angle change from rest in either muscle. The pennation angle of the TB-Long was significantly greater than that of the TB-Med under all conditions. Conclusions: These results suggest that fascicle shortening in the TB-Long muscle occurs in flexion; however, no change was found in the TB-Med. In the upper extremity muscle–tendon complex, the superficial and deeper muscles may have different force-transmission efficiency at flexed joint angles.